Shorinji Kempo Randori: Physiological analysis of West Kalimantan athletes in preparation for the National Sports Week (PON) qualifying rounds - Haetami, Mimi; Ali, Rizki Hazazi; Yunitaningrum, Wiwik; Bafadal, Muhammad Fachrurrozi (Journal Sport Area, 2024)
Background Problems: Physiological demands are very important in supporting both martial arts training and competition. Building on previous research exploring the physiological demands of competitive sports, this study delves into the specific characteristics of Shorinji Kempo athletes, particularly focusing on Randori. Research Objectives: This study aims to examine the physiological characteristics of shorinji kempo randori athletes in West Kalimantan Province, Indonesia. Methods: A descriptive study was conducted on 14 male athletes and 12 female athletes who served as samples in this study. Physiological characteristics are divided into anaerobic performance, which is represented by leg and arm power variables, which are measured using the vertical jump (cm) and medicine ball test (m) instruments, respectively. Then, for aerobic performance, maximum oxygen uptake, or VO2Max (ml/kg/min), is used, which is measured using the multi-level fitness test. This study used quantitative descriptive data analysis, which is seen from the average of each characteristic, both anaerobic and aerobic performance. Findings and Results: The results of the descriptive statistical calculations show the average score of each variable. Each variable is assessed by categorization, so the results are in good and poor categories for several variables. The t-test was conducted to see the difference in the average variables between genders. All variables show a significant difference between male and female athletes (p < 0.05). Furthermore, the results of the Pearson correlation indicated that there was a positive and significant relationship for each variable (p < 0.05). Conclusion: We suggest taking a lab-based test instead of a field test in order to gain more specific data about those physiological aspects. It is hoped that the results of this study can be used as a reference for trainers in creating programmes based on the physiological characteristics of sports and for contributing to the literature on Shorinji Kempo, especially on Randori.